Desenvolvimento de Mimosa caesalpiniaefolia Benth. colonizada com micorrizas arbusculares em solos degradados por mineração de Mn - Garcia, Kaio Gráculo Vieira (2015)
Mineral exploration is considered a major human activities that cause soil pollution with metals, among which is manganese, which when too much can cause toxic symptoms, inhibiting the growth of plants and cause changes in plant communities. In this sense, the search for alternatives to minimize this type of impact is required. A technique considered recent and promising that has been used is phytoremediation, which basically consists of using plants to uptake and accumulation of heavy metals. In this context, the use of plants associated with FMA may improve the uptake of water and nutrients, besides aiding in the plant developing adverse local and contribute to reducing the availability of heavy metals. Thus, the aim of this study was to evaluate the effects of mycorrhizal inoculation in the development of Mimosa caesalpiniaefolia Benth. in soils manganese mining impact. The study was conducted in a greenhouse with experimental design of randomized type in a factorial arrangement 2x2x4, considering: two types of soil (degraded by tailings from the mining Mn and preserved forest); two soil conditions (sterile and natural) and four inoculation treatments (uninoculated (control), inoculated with G. clarum; inoculated with G. etunicatum; inoculated with G. clarum + G. etunicatum (Mix)), with four repetitions. At 60 days after transplanting were evaluated parameters: plant height, stem diameter, number of leaflets, dry matter of shoot and root, length of root system, relative chlorophyll index, spore density of AMF in the soil, root mycorrhizal colonization, mycorrhizal efficiency, macro accumulation (N, P and K) in shoots and manganese in shoot and root and translocation factor. The cultivation on degraded soil by waste of manganese mining reduced the development of thrush plants when compared to cultivated preserved in forest soil, regardless of soil condition and inoculation treatments. Inoculation with G. etunicatum and the Mix, favored the development of plants in sterile condition, regardless of the type of soil, increasing its capacity of tolerance to Mn. The high Mn content in the roots indicate that the thrush (Mimosa caesalpiniaefolia Benth.) May be effective in phytostabilization process in areas degraded by mining Mn.